Delay Along the Care Seeking Journey of Patients with Microbial Keratitis in Uganda. (3rd September 2019) - Arunga, Simon; Kintoki, Guyguy M.; Gichuhi, Stephen; Onyango, John; Newton, Rob; Leck, Astrid; Macleod, David; Hu, Victor H.; Burton, Matthew J.
ABSTRACT: Purpose: To describe the care seeking journey and causes of delay among patients with Microbial Keratitis in Uganda. Methods: A prospective cohort of patients presenting with microbial keratitis at the two main eye units in Southern Uganda (2016–2018). We collected information on demographics, home address, clinical history, and presentation pathway including, order of facilities where patients went to seek care, treatment advice, cost of care, and use of Traditional Eye Medicine. Presentation time was noted. We compared "direct" presenters versus "indirect" presenters and analysed predictors of delay. Results: About 313 patients were enrolled. All were self-referred. Only 19% of the patients presented directly to the eye hospital. Majority (52%) visited one facility before presenting, 19% visited two facilities, 9% visited three facilities, and 2% visited four facilities. The cost of care increased with increase in the number of facilities visited. People in a large household, further distance from the eye hospital and those who used Traditional Eye Medicine were less likely to come directly to the eye hospital. Visiting another facility prior to the eye hospital and use of Traditional Eye Medicine aOR 1.58 (95%CI 1.03–2.43), p = .038 were associated with delayed presentation to the eye hospital. Conclusion: This study provided information on patient journeys to seek care. Delay was largely attributable to having visited another health facility: a referral mechanism for microbial keratitis was non-existent. There is need to explore how these health system gaps can be strengthened.